1984
DOI: 10.1113/jphysiol.1984.sp015104
|View full text |Cite
|
Sign up to set email alerts
|

Early post‐natal development of neuronal function in the kitten's visual cortex: a laminar analysis.

Abstract: SUMMARY1. The normal post-natal development of visual cortical functions was studied by recording extracellularly from 612 single neurones in the striate and parastriate cortex of anaesthetized and paralysed kittens, ranging in age from 6 to 24 days. Analyses have been made of laminar differences in the developmental trends of receptive field properties such as orientation specificity and spatial organization of 'on' and 'off' zones.2. At the beginning of the second post-natal week the majority of neurones (76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
147
2
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(162 citation statements)
references
References 54 publications
12
147
2
1
Order By: Relevance
“…Physiologically, the percentage of binocularly activated neurones in area 17 decreases from about 79 to 60 % from about 2 weeks of age to adult (LeVay et al 1978). Similarly, Albus & Wolf (1984) report about 74% binocularly activated neurones (mostly from area 17 although they include some area 18 neurones in their study) in kittens of similar age. However, the results from studies confined exclusively to area 18 suggest a different developmental process.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Physiologically, the percentage of binocularly activated neurones in area 17 decreases from about 79 to 60 % from about 2 weeks of age to adult (LeVay et al 1978). Similarly, Albus & Wolf (1984) report about 74% binocularly activated neurones (mostly from area 17 although they include some area 18 neurones in their study) in kittens of similar age. However, the results from studies confined exclusively to area 18 suggest a different developmental process.…”
Section: Discussionmentioning
confidence: 93%
“…The X-cell-dominated geniculostriate pathway (to cortical area 17) has served as a useful system with which to study the processes of cortical development including synaptogenesis (Cragg, 1975), maturation of synaptic function (Tsumoto & Suda, 1982), the parcellation of territory by ingrowing geniculocortical afferents (LeVay, Stryker & Shatz, 1978;Shatz & Luskin, 1986;Stryker & Harris, 1986) and the emergence of receptive field (RF) organization Barlow & Pettigrew, 1971;Blakemore & Van Sluyters, 1975;Buisseret & Imbert, 1976;Bonds, 1979;Derrington & Fuchs, 1981;Albus & Wolf, 1984;reviewed in Fregnac & Imbert, 1984;Braastadt & Heggelund, 1985). Although recent reports have described the postnatal development of receptive field properties of neurones in cortical area 18 (Blakemore & Price, 1987;Milleret, Gary-Bobo & Buisseret, 1988), little is known of the structural development of this cortical area and its major thalamic input.…”
Section: Introductionmentioning
confidence: 99%
“…3A are shown in Fig. 3 BJ-B3 kittens have reported broader tuning than in the adult (3,4,6,(44)(45)(46)(47)(48).…”
mentioning
confidence: 88%
“…On the basis of results from this present study and from previous work (Blakemore & Van Sluyters, 1975;Bonds, 1979;Albus & Wolf, 1984) it appears that a population of innately determined, clearly orientation-selective cells exists in area 17 in very young normal but visually inexperienced kittens. Blakemore & Van Sluyters (1975) suggested that innate orientation selectivity in area 17 is largely determined by inputs from geniculate X cells.…”
Section: Area 18 In Visually Deprived Catmentioning
confidence: 68%